Factors Affecting the Repurchase Intention in E-Commerce in Kathmandu Valley: Higher Order Structural Analysis Using PLS-SEM - Sapkota, Anamol; Adhikari, Simran (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: The purpose of this study is to examine the influence of convenience on repurchase intention in Nepal’s e-commerce sector, with a focus on the mediating roles of perceived value and customer satisfaction.Design/methodology/approach: This study adopts a positivist research philosophy, utilizing quantitative methods and statistical analysis to investigate the relationships between convenience, perceived value, satisfaction, and repurchase intention in e-commerce. A causal-comparative design was used to examine the structural relationship and data was gathered from 273 respondents through self-administered survey. SMART-PLS 4.0 was used to analyzed the data.Findings: The findings indicate that convenience has a positive yet modest impact on repurchase intention. While perceived value does not mediate the relationship between convenience and repurchase intention, customer satisfaction significantly mediates this relationship highlighting the importance of satisfaction in driving repurchase behavior.Conclusion: The study highlights the importance of improving convenience in search and evaluation for customer satisfaction and perceived value, driving repurchase intention in Nepal’s e-commerce sector, highlighting the need for holistic userexperience optimization.Implications: This study contributes to the understanding of e-commerce consumer behavior in Nepal by highlighting the significant role of search and evaluation convenience in enhancing customer satisfaction and repurchase intention. It providespractical recommendations for e-commerce platforms to optimize user experience by simplifying search processes and improving product evaluations, ultimately fostering customer loyalty and driving sustainable business growth. JEL Classification: L81, L86, M31, O33